ORGANIZATION OF PHYSICAL EDUCATION OF STUDENTS IN GROUP AND OUT-OF-CLASS WORK - Гончар, Галина; Затуливітер, Анастасія (SWorldJournal, 2024)
The development of mass physical culture and sports in educational institutions is aimed, first of all, at strengthening the health of students, physical development and motor activity. In order to reach a larger number of students, it is necessary to in